Professional development of teachers: Perceptions and challenges of foundation phase teachers - Thokozane P. Dyosini (South African Journal of Childhood Education)
Background: South Africa’s teacher retention crisis calls for policy makers, school leaders and teachers to explore ways for professional growth. This study examined six novice teachers’ experiences and views on continuous professional development (CPD) and how it benefits teachers as they transition from mentees to mentors.